Pengaruh Distorsi Harmonik pada Compact Fluorescent Lamps - Setyaningsih, Endah; Suharto, Hang; Christian, Christian (TESLA: Jurnal Teknik Elektro, 2016)
Compact Fluorescent Lamps (CFL) are one of the non-linear load which depicts distorted wave containing harmonics. Harmonics are integer multiplication periodically of the fundamental frequency. Harmonics will worsen the quality of Compact Fluorescent Lamps, one of the results is shorten the lamp life due to excessive overheating. Harmonics can be calculated with Total Harmonic Distortion. This study discusses the effect of harmonic distortion on Compact Fluorescent Lamps, and make Low Pass Filter for reducing THD value. Tests were conducted in this study are testing the effect of the value of  to the value of power factor, the ratio of THD value, power factor and illumination of the expensive one with the cheap one. Based on the results of tests that have been carried out, the value of  has a negative effect on the value of the power factor. THD and power factor value in expensive lamps has no significant difference with cheap lamps, while the value of illumination on the expensive lamps have significant differences with cheap lamps. and illumination value of the lamps that have not been fitted with filters are bigger than the lamps that have been fitted with a filter, and the filter successfully reduce 88,03%  value of Compact Fluorescent Lamps.